Comparison of bone marrow-derived and mucosal mast cells in controlling intramacrophage Francisella tularensis replication - Hunter, Colleen (2012)
Although the importance of mast cells (MCs) in response to allergens has been characterized extensively, the contribution of these cells in host defense against bacterial pathogens is not well understood. Previously, we have demonstrated that the release of interleukin-4 by bone marrow-derived MCs inhibits intramacrophage replication of Francisella tularensis live vaccine strain (LVS). Because pneumonic tularemia is one of the several manifestations of infection by Francisella, it is important to determine whether MCs present in mucosal tissues, i.e. the lung, exhibit similar effects on LVS replication. On the basis of this rationale, we phenotypically compared mucosal mast cells (MMCs) to traditional bone marrow-derived MCs. Both cell types exhibited similar levels of cell surface expression of fragment crystal epsilon receptor I (FcεRI), mast/ stem cell growth factor receptor (c-Kit) and major histocompatibility complex I (MHCI), as well as patterns of granulation. MMCs exhibited a comparable, but somewhat greater uptake of fluorescent-labeled beads compared with MCs, suggesting an increased phagocytic ability. MCs and MMCs co-cultured with primary macrophages exhibited comparable significant decreases in LVS replication compared with macrophages cultured alone. Collectively, these results suggest that MMCs are phenotypically similar to MCs and appear equally effective in the control of intramacrophage F. tularensis LVS replication.